A Strategy for Neutral Voltage Modulation Ensuring Fault Tolerance in CHB Multilevel Inverters With Reduced CMV and Unbalanced DC Sources - Thawat Sornsadaeng; Peerapon Chanhom; Damrong Amorndechaphon; Siriroj Sirisukprasert (IEEE Access)
This paper introduces a fault-tolerant control method for Cascaded H-Bridge Multilevel Inverters (CHB MLI) using Neutral Voltage Modulation (NVM), enabling reliable operation even when DC source modules are damaged or operating at reduced voltage. The method calculates the inverter’s modulating signals based on the lowest and middle DC source voltages of each phase, followed by the calculation and injection of a common-mode voltage (CMV) modulating signal, which is minimized or nullified. This approach effectively reduces CMV and prevents overmodulation by regulating the control signal to remain within the available module voltage, ensuring balanced three-phase output with low Total Harmonic Distortion (THD). Moreover, the method adapts to unbalanced DC source conditions by dynamically adjusting the inverter’s modulating signals in response to voltage changes, offering a more comprehensive solution compared to traditional NVM techniques. The proposed method is validated through simulations and experiments with an asymmetrical three-phase CHB MLI using Resistive-Inductive (RL) loads. Results confirm its robustness and efficiency across various fault scenarios and operating conditions, demonstrating its potential to significantly enhance system reliability, stability, and performance in industrial applications.